Algorithmic Component Ablation Analysis. - Kewei Wang (556371) (2025)
(A) Performance comparison across five algorithm configurations with 95% confidence intervals and statistical significance markers (***p < 0.001). (B) Individual component contributions to total algorithmic improvement, showing cumulative effects and synergy analysis.